Neonatal Treatment with a Pegylated Leptin Antagonist Induces Sexually Dimorphic Effects on Neurones and Glial Cells, and on Markers of Synaptic Plasticity in the Developing Rat Hippocampal Formation. (August 2015) - López‐Gallardo, M.; Antón‐Fernández, A.; Llorente, R.; Mela, V.; Llorente‐Berzal, A.; Prada, C.; Viveros, M. P.
<x xml:space="preserve">Abstract</x> The present study aimed to better understand the role of the neonatal leptin surge, which peaks on postnatal day (PND)9–10, on the development of the hippocampal formation. Accordingly, male and female rats were administered with a pegylated leptin antagonist on PND9 and the expression of neurones, glial cells and diverse markers of synaptic plasticity was then analysed by immunohistochemistry in the hippocampal formation. Antagonism of the actions of leptin at this specific postnatal stage altered the number of glial fibrillary acidic protein positive cells, and also affected type 1 cannabinoid receptors, synaptophysin and brain‐derived neurotrophic factor (BDNF), with the latter effect being sexually dimorphic. The results indicate that the physiological leptin surge occurring around PND 9–10 is critical for hippocampal formation development and that the dynamics of leptin activity might be different in males and females. The data obtained also suggest that some but not all the previously reported effects of maternal deprivation on hippocampal formation development (which markedly reduces leptin levels at PND 9–10) might be mediated by leptin deficiency in these animals.